FORMULASI GEL EKSTRAK DAUN KEMANGI (Ocinum Sanctum L.) SEBAGAI SEDIAAN HAND SANITIZER TAHUN 2022 - Kemal, Amir (Journal of Pharmacy Tiara Bunda, 2022)
The formulation has been carried out antiseptic hand gel preparation of the ethanol extract of leaves of basil (Ocimum sanctum L.) using a combination of Carbopol 940 and HPMC base accompanied by physical stability test preparation gel. This study aims to determine the physical stability of the combination of base and determine the concentration of a good combination of base carbopol 940 and HPMC in antiseptic hand gel formulation ethanol extract of basil (Ocimum sanctum L.). Physical stability of the gel formulation is determined by observation of changes in color, smell, shape, pH, homogeneity, and syneresis. The results showed that sediaaan antiseptic hand gel can be said to be stable on the parameters of homogeneity where there are no solid particles in the preparation. Sinersis stable in which there is no liquid on the surface of the gel. Stable in good dispersive power parameters, namely Formula I, II, and III have the diameter of no more than 3-5 cm. While the results of the measurement of pH, a combination of carbopol 940 gel preparations and HPMC with a concentration of 0.5% and 0.25% of its pH is stable in storage and has a pH in accordance with the physiological skin pH is 4.5-6.5. Based on the results obtained, the base 940 and HPMC carbopol combination with a concentration of 0.5% and 0.25% had good physical stability